A business plan- Bio based farm producing meat for the Czech market - Said, Jana; Kubíček, Aleš; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor's thesis outlines a business plan for BioFarmaso, an Organic certified beef farm organized at a sustainable basis in South Bohemia, Czech Republic. The thesis will seek to build a profitable but ecofriendly business model for producing high quality organic beef that will serve the increasing demand for ethically sourced meat in the local market. For this purpose, the study has used a variety of analytical tools such as PEST and SWOT analysis, Porter’s five forces and Business Model Canvas to evaluate the market, competitive position, and viability of the business. In addition, the thesis addresses the practical strategies in managing costs, operations, and customer relationship management to ensure long term business success. This business plan combines a theoretical aspect of planning and practical planning to place BioFarmaso as the key player of the organic beef on the Czech market.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses